Pembelajaran Montessori Islami sebagai Sarana Pembentukan Kepribadian Islam yang Utuh pada Anak TK - Ridwan Hermawan; Nalita Septyarani; Vera Siti Maghfiroh; Emat Muslihat (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The character crisis and the weakening of Islamic understanding among the younger generation have become serious issues that need to be addressed starting from early childhood education. Kindergarten children are at a phase of fitrah development, which significantly determines the formation of their personality in the future. Islamic education is expected to provide a comprehensive solution in shaping the child's personality from an early age, balancing cognitive, emotional, social, and spiritual aspects. This study aims to examine the theoretical implementation of Islamic Montessori learning as a means of forming an integral Islamic personality in early childhood. Using a literature review approach and qualitative content analysis, this study examines various theories, previous research findings, and expert views sourced from books, journals, and scientific works related to early childhood education and Islamic education. The results show that Islamic Montessori significantly contributes to the development of an integral Islamic personality. Children not only develop cognitively and psychomotorically but also become accustomed to the habits of worship, discipline, responsibility, empathy, and respect for others. Through a conducive learning environment and direct practices of Islamic life, Islamic Montessori serves as a strategic tool in preparing a Muslim generation that is faithful, noble in character, with strong Islamic personality and independence.